Comparison of programmed intermittent bolus infusion and continuous infusion for postoperative patient-controlled analgesia with thoracic paravertebral block catheter: a randomized, double-blind, controlled trial. Issue 2 (February 2019) - Chen, Lulu; Wu, Yiquan; Cai, Yaoyao; Ye, Yingchao; Li, Li; Xia, Yun; Papadimos, Thomas J; Xu, Xuzhong; Wang, Quanguang
Abstract : Background and objectives: In this randomized, double-blind, controlled study, we hypothesized that programmed intermittent bolus infusion (PIBI) of local anesthetic for continuous paravertebral block (PVB), combined with patient-controlled analgesia (PCA), provided better pain control, better patient satisfaction, and decreased in local anesthetic consumption when compared with a continuous infusion (CI) combined with PCA, after video-assisted thoracoscopic unilateral lung resection surgery. Methods: Preoperatively, patients undergoing video-assisted thoracoscopic unilateral lung resection surgery received ipsilateral paravertebral catheters inserted at the level of thoracic vertebrae 4 and 5. All the subjects received an initial bolus of 15 mL 0.375% ropivacaine via the catheters. Subjects were randomized to receive 0.2 % ropivacaine 8 mL/h as either PIBI (n=17) or CI (n=17) combined with a PCA pump. The pain scores, frequency of PCA, local anesthetic consumption, patient satisfaction, and the need for rescue analgesia with tramadol were recorded until 48 hours postoperative. Results: The numeric rating scale scores in the PIBI group were significantly lower than the CI group at 4, 8, 12 hours and 4, 8, 12, 24 hours postoperatively, at rest, and during coughing, respectively. PCA local anesthetic consumption (30 mg (20–60 mg) vs 120 mg (70–155 mg), p=0.000) and frequency of PCA use over 48 hours (3 (2–6) vs 12 (7–15.5), p=0.000) was lower in the PIBI group as compared with the CI group. Additionally, the PIBI group showed greater patient satisfaction. The need for tramadol rescue was similar in the two groups. Conclusions: In PVBs, local anesthetic administered as a PIBI in conjunction with PCA provided superior postoperative analgesia to a CI combined with PCA in patients undergoing video-assisted thoracoscopic unilateral lung resection surgery. Clinical trial registration: ChiCTR-IOR-17011253.